FEATURES OF THE PROFESSIONAL DEVELOPMENT OF TEACHING EMPLOYEES OF PROFESSIONAL COLLEGES IN THE CONDITIONS OF MODERN CHALLENGES (Innovative professional education, 2024)
The study is devoted to the analysis of the peculiarities of college teachers’ professional competence development in the conditions of current challenges. The psychologicalstructure of the phenomenon and the components of the teacher’s professional activity were taken into account. In addition, the continuity, purposefulness and systematicity of the process of college teachers’ professional development were highlighted. The process should combine the possibilities of formal (advancement courses, internships); non-formal (development in the college environment) and informal education (professional self-improvement).
Keywords: teacher’s professional competence, vocational higher education, quality of education, formal education, non-formal education, informal education